2013
DOI: 10.1186/2193-1801-2-579
|View full text |Cite
|
Sign up to set email alerts
|

Endophytic fungi from the Amazonian plant Paullinia cupana and from Olea europaea isolated using cassava as an alternative starch media source

Abstract: Endophytic fungi live inside plants, apparently do not cause any harm to their hosts and may play important roles in defense and growth promotion. Fungal growth is a routine practice at microbiological laboratories, and the Potato Dextrose Agar (PDA) is the most frequently used medium because it is a rich source of starch. However, the production of potatoes in some regions of the world can be costly. Aiming the development of a new medium source to tropical countries, in the present study, we used leaves from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 43 publications
2
13
1
Order By: Relevance
“…cupana ( Table 2 ). The genera Diaporthe , Pestalotiopsis and Phomopsis were previously identified in endophytic communities of phyllospheres [ 29 ]. Thus, we hypothesize that endophytic fungi that colonize P .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…cupana ( Table 2 ). The genera Diaporthe , Pestalotiopsis and Phomopsis were previously identified in endophytic communities of phyllospheres [ 29 ]. Thus, we hypothesize that endophytic fungi that colonize P .…”
Section: Resultsmentioning
confidence: 99%
“…Some studies have reported the endophytic fungal diversity of P . cupana leaves [ 18 , 29 , 30 ] and endophytic bacterial diversity of P . cupana leaves, seeds and roots [ 31 , 32 ].…”
Section: Introductionmentioning
confidence: 99%
“…Some endophytic fungi have specific growth requirements and some species are not adapted to grow and sporulate in artificial culture media. Sometimes the fast growing fungal species outcompete the slower growing species [ 20 ]. Therefore use of several media with different nutrient aspects may probably be an advantage in isolating a large number of endophytic fungi including the cryptic species from the plant tissue.…”
Section: Resultsmentioning
confidence: 99%
“…Climate change scenarios foresee temperatures increases in many Mediterranean regions [21], revealing the importance of such studies. Most research on olive tree phyllosphere microbiota has mainly focused on fungal communities, either exclusively on endophytic [22][23][24][25] or both endophytic and epiphytic populations [26]. As far as we know, there are only one study focusing on archaeal and bacterial diversity in olive tree phyllosphere [27].…”
Section: Introductionmentioning
confidence: 99%